2020
DOI: 10.1167/iovs.61.10.26
|View full text |Cite
|
Sign up to set email alerts
|

Trehalose Induces Autophagy Against Inflammation by Activating TFEB Signaling Pathway in Human Corneal Epithelial Cells Exposed to Hyperosmotic Stress

Abstract: et al. Trehalose induces autophagy against inflammation by activating TFEB signaling pathway in human corneal epithelial cells exposed to hyperosmotic stress. Invest

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 61 publications
1
27
0
Order By: Relevance
“…These protective effects were further enhanced when rapamycin enhanced autophagy activation in hypertonic HCECs (Liu et al, 2020a). In addition, they suggest that trehalose, as an autophagy enhancer, induces autophagy antiinflammation by inhibiting Akt activation of transcription factor EB in primary HCECs exposed to high osmotic stress (Liu et al, 2020b). The mechanism of trehalose inhibition of inflammation is independent of NFκB pathway, and it may reduce stress-induced inflammation by inhibiting p38MAPK and activating autophagy (Panigrahi et al, 2019).…”
Section: Autophagy and Inflammationmentioning
confidence: 92%
“…These protective effects were further enhanced when rapamycin enhanced autophagy activation in hypertonic HCECs (Liu et al, 2020a). In addition, they suggest that trehalose, as an autophagy enhancer, induces autophagy antiinflammation by inhibiting Akt activation of transcription factor EB in primary HCECs exposed to high osmotic stress (Liu et al, 2020b). The mechanism of trehalose inhibition of inflammation is independent of NFκB pathway, and it may reduce stress-induced inflammation by inhibiting p38MAPK and activating autophagy (Panigrahi et al, 2019).…”
Section: Autophagy and Inflammationmentioning
confidence: 92%
“…It has also been shown that osmoprotectants also reduce matrix metalloproteinase (MMP) synthesis and oxidative stress and can regulate the autophagic process [ 45 , 46 , 47 ]. Overall, osmoprotectants appear effective in preventing ocular surface cell apoptosis induced by DED.…”
Section: Types and Roles Of Ingredients Used In Tear Substitutesmentioning
confidence: 99%
“…Melatonin-loaded polymer polyvinyl caprolactam-polyvinyl acetate-polyethyleneglycol graft copolymer micelles ameliorated hyperosmolarity-induced ocular surface damage of DED via phosphated and tension homology deleted on chromosome ten-induced kinase 1-mediated mitophagy [ 46 ]. Trehalose, as an autophagy activator, also reduced the expression of pro-inflammatory mediators TNF-α, IL-1β, IL-6, and IL-8 via transcription factor EB (TFEB) activation in vitro DE model [ 47 ]. The active form of vitamin D3, calcitriol, also augmented autophagy flux and inhibited apoptosis and inflammation via vitamin D receptor signaling pathway to prevent ocular injury and clinical complication caused by DE [ 48 ].…”
Section: Research Progress Of Exosomes and Autophagy In Ocular Surfac...mentioning
confidence: 99%